Understanding seed selection decisions among small-scale maize farmers in Machakos County, Kenya: the dominance of market leader varieties - Mawia, Harriet; Mburu, John; Chimoita, Evans; Rutsaert, Pieter (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe maize seed market in Kenya is highly competitive, yet older varieties dominate smallholder farmers’ preferences. The current study aimed to identify the key drivers of maize seed selection by examining trait priorities, prior experience, purchase behavior, and sociodemographic profiles of farmers across different seed variety groups.MethodsFarmers were categorized into three groups based on their preferred maize varieties: market leader, competitor, and low-cost. A multinomial logit model was used for inferential analysis.ResultsThe results revealed that 70% of the farmers preferred market leader varieties, while 21% preferred competitor varieties and 7% chose low-cost varieties. Drought tolerance emerged as the most valued trait, reported by 72% of farmers. In addition, farmers reported little experience with different maize seed varieties and hybrids. Trait preferences, previous knowledge and farm size primarily significantly influenced seed selection. Regarding purchasing behavior, most farmers made quick decisions at a mock agro-dealer store, often disregarding price offers and informational posters when their preferred variety was available.DiscussionThis study provides a basis for developing strategies that encourage and influence farmers to broaden their maize seed choice considerations which will ultimately improve domestic maize production as climate change continues. It aimed to understand better the factors influencing farmers’ loyalty to market leader maize varieties in Machakos County, Kenya.